BIAYA DAN MANFAAT PENGADAAN PROGRAM ASTRA DAIHATSU PRODUCTION PLANNING SYSTEM (ADPPS) DI PT ADM - Hartono, Gunawarman (Industrial and Systems Engineering Assessment Journal (INASEA), 2009)
PT ADM has implemented technology in carrying out its business activity. One of it is located in the Production Control department in cooperation with the Corporate Information Technology department, namely Astra Daihatsu Production Planning System. Although the ADDPS application has benefited for company, the benefit gained from this application could not be economically measured. This study aims to analyze the feasibility of the implementation of the ADDPS application at company and analyze the amount of benefit obtained from the implementation of the application. Research methods used are literature review, observation, questionnaire, and analytical methods. Data was analysed using Economic Techniques (Simple ROI, NPV) and Information Economics Scorecard, it can be concluded that the implementation of the ADPPS system at company is feasible. This conclusion obtained from the implementation of ADPPS application may be used as a basic reference for other investment projects, for its cost and benefit.